Behavioral Problems Perceived by the Alcoholic and His Family - A Study among Males in Rural Areas - Srinath, Ramamurthy (International Journal of Psychosocial Rehabilitation, 2017)
While alcohol use is deeply embedded in many societies, recent years have seen changes in drinking patterns across the world. Rates of consumption, drinking to excess among the general population and heavy episodic drinking among young people are on the rise in many countries. Health problems associated with alcohol consumption have reached alarming levels, and alcohol use contributes to a wide range of diseases, health conditions and high-risk behaviors, mental disorders, loss of productivity, road traffic injuries, liver diseases and spousal violence. Although the prevalence of alcoholism among rural males in Tamil Nadu, India had been reported, but there is a lack of information regarding the prevalence of various types of alcoholism and problem drinking along with the psychosocial and economic aspects of drinking, especially in this part of the region. To highlight these problems the various types of alcoholism and problem have been extensively analyzed in this study.